The Cameron-Clegg Coalition: Lessons Learned?. (April 2015) - Heppell, Timothy
The May General Election is widely expected to deliver a hung Parliament, increasing the likelihood of another coalition government.Timothy Heppell considers the lessons learnt from the 2010 coalition negotiations for both junior and senior coalition partners.